The next steps in improving the outcomes of advanced ovarian cancer. (June 2015) - Openshaw, Mark R; Fotopoulou, Christina; Blagden, Sarah; Gabra, Hani
Worldwide ovarian cancer affects over 200, 000 women per year. Overall survival rates are poor due to two predominate reasons. First, the majority of patients present with advanced disease creating significant difficulty with effecting disease eradication. Second, acquisition of chemotherapy resistance results in untreatable progressive disease. Advances in treatment of advanced ovarian cancer involve a spectrum of interventions including improvements in frontline debulking surgery and combination chemotherapy. Anti-angiogenic factors have been shown to have activity in frontline and recurrent disease while novel chemotherapeutic agents and targeted treatments are in development particularly for disease that is resistant to platinum-based chemotherapy. These developments aim to improve the progression-free and overall survival of women with advanced ovarian cancer